2021
DOI: 10.3892/or.2021.8151
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‑7515 suppresses pancreatic cancer cell proliferation, migration and invasion via downregulating IGF‑1 expression

Abstract: Pancreatic cancer (PC) is a lethal malignancy of the gastrointestinal tract. Previous studies have reported that microRNAs (miRNAs/miRs) are involved in the tumorigenesis of PC. Therefore, the present study aimed to determine the effects of miR-7515 on PC cell proliferation, invasion and migration in vitro and in vivo, and investigate its underlying molecular mechanism using bioinformatics, double luciferase assay and western blotting. The results revealed that the expression levels of miR-7515 were downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…[ 55 ] Previous studies have indicated that oxidative stress induced by PPARγ activation is mainly responsible for cancer inhibition. [ 56–58 ] In this study, we found that ORI significantly downregulated ALDOA, ENO1, and IGF‐1, whereas upregulated PPARγ protein expression at the cellular level. A more convincing manifestation was that the inhibitory effect of ORI was still present after siRNA interfered with the expression of ALDOA and ENO1.…”
Section: Discussionmentioning
confidence: 54%
“…[ 55 ] Previous studies have indicated that oxidative stress induced by PPARγ activation is mainly responsible for cancer inhibition. [ 56–58 ] In this study, we found that ORI significantly downregulated ALDOA, ENO1, and IGF‐1, whereas upregulated PPARγ protein expression at the cellular level. A more convincing manifestation was that the inhibitory effect of ORI was still present after siRNA interfered with the expression of ALDOA and ENO1.…”
Section: Discussionmentioning
confidence: 54%
“…IGF-1 is a polypeptide hormone belonging to the growth factor hormone family that helps control the growth and development of organs, muscles, and tissues in the body, besides, it is also involved in regulating glucose metabolism and brain function, IGF-1 assists with natural bodily development, while abnormal accumulation of IGF-1 can negatively affect health [25]. Currently, IGF1 was found to be involved in many cancers, such as lung cancer [26], cervical cancer [27], pancreatic cancer [28], and esophageal carcinoma [29]. In breast cancer, IGF-1 gene polymorphism was associated with an increased risk for this cancer [30].…”
Section: Discussionmentioning
confidence: 99%